Bacterial and Archaeal Communities in Polymetallic Nodules, Sediments, and Bottom Waters of the Abyssal Clarion-Clipperton Zone: Emerging Patterns and Future Monitoring Considerations - Wear, Emma K.; Church, Matthew J.; Orcutt, Beth N.; Shulse, Christine N.; Lindh, Markus V.; Smith, Craig R. (Frontiers in Marine Science, 2021)
Bacteria and archaea are key contributors to deep-sea biogeochemical cycles and food webs. The disruptions these microbial communities may experience during and following polymetallic nodule mining in the Clarion-Clipperton Zone (CCZ) of the North Pacific Ocean could therefore have broad ecological effects. Our goals in this synthesis are to characterize the current understanding of biodiversity and biogeography of bacteria and archaea in the CCZ and to identify gaps in the baseline data and sampling approaches, prior to the onset of mining in the region. This is part of a large effort to compile biogeographic patterns in the CCZ, and to assess the representivity of no-mining Areas of Particular Environmental Interest, across a range of taxa. Here, we review published studies and an additional new dataset focused on 16S ribosomal RNA (rRNA) gene amplicon characterization of abyssal bacterial and archaeal communities, particularly focused on spatial patterns. Deep-sea habitats (nodules, sediments, and bottom seawater) each hosted significantly different microbial communities. An east-vs.-west CCZ regional distinction was present in nodule communities, although the magnitude was small and likely not detectable without a high-resolution analysis. Within habitats, spatial variability was driven by differences in relative abundances of taxa, rather than by abundant taxon turnover. Our results further support observations that nodules in the CCZ have distinct archaeal communities from those in more productive surrounding regions, with higher relative abundances of presumed chemolithoautotrophic Nitrosopumilaceae suggesting possible trophic effects of nodule removal. Collectively, these results indicate that bacteria and archaea in the CCZ display previously undetected, subtle, regional-scale biogeography. However, the currently available microbial community surveys are spatially limited and suffer from sampling and analytical differences that frequently confound inter-comparison; making definitive management decisions from such a limited dataset could be problematic. We suggest a number of future research priorities and sampling recommendations that may help to alleviate dataset incompatibilities and to address challenges posed by rapidly advancing DNA sequencing technology for monitoring bacterial and archaeal biodiversity in the CCZ. Most critically, we advocate for selection of a standardized 16S rRNA gene amplification approach for use in the anticipated large-scale, contractor-driven biodiversity monitoring in the region.